Mango dry matter content at harvest to achieve high consumer quality of different cultivars in different growing seasons. - FREITAS, S. T. de (2022)
Dry matter content (DMC) at harvest has been shown to be highly correlated with soluble solids content (SSC), which determines consumer acceptance of ripe mango. However, studies are required to evaluate the stability of the relationship among DMC x SSC x consumer acceptance for different mango cultivars under different climatic/seasonal growing conditions. The hypothesis of our study was that the minimum mango DMC required to achieve high consumer quality and acceptance is highly affected by the cultivar and climatic/seasonal growing conditions. The objective of this study was to determine the fruit DMC at harvest required to achieve high consumer quality and acceptance for Palmer and Tommy Atkins mangoes produced during the summer and winter growing seasons in the Sao Francisco Valley, Brazil.